An Investigation Into The Relationship Between Birth Weight And Maternal, Placental, And Demographic Factors (Journal of Pharmaceutical Negative Results, 2022)
The health of the mother and the anatomy of the placenta are the two key characteristics that are known to connect with low birth weight. The mother's health is essential to the development of the foetus. On the other hand, the placenta has to be fully grown and in good health in order for it to be able to transport all of the nutrients that are present in the mother to the developing baby. At the Maternity unit, a prospective study was carried out on a total of 180 moms who had recently given birth. Each mother in turn was asked to participate in the study when her child was being admitted, and this continued until the desired number of participants was reached. Among mothers who were over the age of 25, had an education level that was lower than higher secondary, and had a family income that was less than 15,000 rupees, correspondingly 33.3%, 35%, and 29.2% of their babies were born LBW. The level of schooling a mother had was found to have a significant association with her child's birth weight (p = 0.053). 36.6% of LBW babies were delivered to women who had a history of preeclampsia (12.20), and 42.9% of LBW babies were given to moms who had a history of diabetes (3.9). 31.1% of babies born to moms who had caesarean sections (which made up 50% of all deliveries) and multigravid mothers (which made up 46.7% of all deliveries) were born LBW. There was a statistically significant difference discovered between the gestational age of the mother and the baby's birth weight (p 0.001) According to the findings of the study, the risk factors for low birth weight babies are as follows: maternal age, low education and income, any chronic medical conditions, gestational age, and morphometric placental characteristics. According to the findings of this study, there is a strong association between the morphmetric characteristics of the placenta and the birth weight.